Simultaneous Determination of Cadmium and Lead in Medicinal Plants Using Graphite Furnace Atomic Absorption Spectrometry and Direct Slurry Sampling - Fortunato, Felipe Manfroi [UNESP]; Gomes Neto, José Anchieta [UNESP]; Giovanni Freschi, Gian Paulo (Perkin-elmer Corp, 2012)
A method is proposed for the simultaneous determination Cd and Pb in medicinal plants using direct slurry sampling by GF-AAS. The thermal behavior of analytes was checked in aqueous and slurry media using Ir permanent modifier. The optimized pyrolysis (1000 degrees C) and atomization (2200 degrees C) temperatures allowed calibration using aqueous standards.For a 20-mu L injected volume, the calculated characteristic mass was 1.8 pg for Cd and 59 pg for Pb. The relative standard deviation (n=12) for Cd and Pb was 5.3% and 3.5%, respectively. The limit of detection was 0.12 mu g 1,1 for Cd and 1.22 mu g L-1 for Pb. Accuracy was checked by analyzing the standard reference materials Ginkgo Biloba Leaves, Peach Leaves, and Pine Needles. The results obtained for the analytes were in agreement with the certified values at the 95% confidence level. Ten medicinal plant samples were analyzed and the found concentrations ranged from 0.19-0.34 mu g g(-1) for Cd and 1.02-1.91 mu g g(-1) for Pb.